Control design for switched port-controlled Hamiltonian systems with unstabilizable modes: An improved mode-dependent average dwell time scheme. (November 2020) - Wang, Zi-Ming; Wei, Airong; Zhao, Xudong; Mu, Rui; Zhang, Xianfu
Abstract: In this paper, the stabilization and H ∞ control are considered for switched port-controlled Hamiltonian systems (SPCHSs) with unstabilizable modes via energy-based multiple Lyapunov functions (MLFs) methods and mode-dependent average dwell time (MDADT) strategies, where an improved MDADT-based tradeoff method is developed by a time subsequence technique to govern the running time of the asymptotic stabilization modes and the other ones. Firstly, based on the mode-dependent state feedback controllers, stabilization conditions are derived for SPCHSs with unstabilizable modes under a new MDADT scheme. Secondly, for the case that there are external disturbances for the system, the mode-dependent H ∞ controllers are designed to attenuate external disturbances, besides, H ∞ control conditions are achieved for the system by the energy-based MLFs method with the designed MDADT scheme. Finally, two simulation examples are presented to demonstrate the effectiveness of the proposed methods.